2020
DOI: 10.1101/2020.07.06.168179
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

PAK3 controls the tangential to radial migration switch of cortical interneurons by coordinating changes in cell shape and polarity

Abstract: SUMMARYDuring the embryonic development, cortical interneurons migrate a long distance tangentially and then re-orient radially to settle in the cortical plate where they contribute to cortical circuits. Migrating interneurons express PAK3, a p21-activated kinase that switches between active and inactive states and controls interneuron migration by unknown mechanism(s). Here we examined the role of the kinase activity of PAK3 to regulate the migration of cortical interneurons. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 70 publications
(113 reference statements)
0
4
0
Order By: Relevance
“…At any location along the tangential streams, a proportion of interneurons can re-orient radially in order to leave the tangential paths and to integrate the cortical plate (CP). This "tangential-to-radial switch" of migration represents a major directional change operated by migrating cortical interneurons to reach their cortical target 47 . Among the guidance cues required for cortical interneurons to migrate in the embryonic cortex, the CXCL12 chemokine secreted by the MZ and by cortical progenitors in the SVZ/IZ (intermediate zone), promotes the cortical interneuron tangential migration within the deep and superficial tangential migratory streams through binding to the CXCR7 and CXCR4 receptors 22,23,[48][49][50][51][52][53] .…”
Section: Cxcl12 Modulates the Respective Camp And Cgmp Levels In The ...mentioning
confidence: 99%
“…At any location along the tangential streams, a proportion of interneurons can re-orient radially in order to leave the tangential paths and to integrate the cortical plate (CP). This "tangential-to-radial switch" of migration represents a major directional change operated by migrating cortical interneurons to reach their cortical target 47 . Among the guidance cues required for cortical interneurons to migrate in the embryonic cortex, the CXCL12 chemokine secreted by the MZ and by cortical progenitors in the SVZ/IZ (intermediate zone), promotes the cortical interneuron tangential migration within the deep and superficial tangential migratory streams through binding to the CXCR7 and CXCR4 receptors 22,23,[48][49][50][51][52][53] .…”
Section: Cxcl12 Modulates the Respective Camp And Cgmp Levels In The ...mentioning
confidence: 99%
“…More specifically, Dyrk1a controls the frequency of nucleokinesis and the amplitude of the forward progression of nuclei during these events, likely contributing to the net decrease of migration we observe in both mutants (Dyrk1a DlxCre/+ and Dyrk1a K188R/+ ). Abnormalities in INs development have been commonly associated with neurodevelopmental disorders 64 and lately several studies have demonstrated that migration defects contribute to the etiology of conditions like ID and ASD [65][66][67][68][69] . Reduced production of INs cell types and migration defects were also described in GABAergic neurons derived from DS iPSCs 61 , and proposed as being partly responsible for the reduced number of INs observed in DS brains.…”
Section: Dyrk1a Haploinsufficiency In Interneurons Leads To Behaviora...mentioning
confidence: 99%
“…At any location along the tangential streams, a proportion of interneurons can reorient radially in order to leave the tangential paths and to integrate the cortical plate (CP). This "tangential-to-radial switch" of migration represents a major directional change operated by migrating cortical interneurons to reach their cortical target 48 . Among the guidance cues required for cortical interneurons to migrate in the embryonic cortex, the CXCL12 chemokine secreted by the MZ and by cortical progenitors in the SVZ/IZ (intermediate zone), promotes the cortical interneuron tangential migration within the deep and superficial tangential migratory streams through binding to the CXCR7 and CXCR4 receptors 22,23,[49][50][51] .…”
Section: Cxcl12 Modulates the Respective Camp And Cgmp Levels In The ...mentioning
confidence: 99%